Construction of nitrogen critical dilution curve and differences in nitrogen nutrition characteristics in different organs of maize varieties with contrasting nitrogen efficiencies - Bao, Shuqin; Chai, Xingying; Liao, Linzheng; Li, Xiaoying; Shi, Lin; Dong, Xixi; Long, Sida; Li, Huifu; Wang, Hanyu; Li, Zhenghong; Wang, Mengting; Ren, Yun; et al. (Frontiers in Plant Science, 2025)
IntroductionThis study aimed to establish and verify a critical nitrogen dilution model for different organs of maize varieties with different nitrogen efficiencies and clarify differences in nitrogen nutritional characteristics.MethodsTwo maize varieties (nitrogen-efficient variety ZH 311 and nitrogen-inefficient variety XY 508) were grown under four nitrogen levels to evaluate N dynamics and dry matter accumulation.ResultsThe results showed that the critical nitrogen concentration dilution curves based on root dry matter, stem-sheath dry matter, leaf dry matter, and plant dry matter, with coefficient of determination (R²>0.90), all reached significant levels and could be used for nitrogen nutrition diagnosis of maize. However, a and b values of the critical nitrogen concentration models for different organs differed significantly; e.g., the root model had the lowest a value and the leaf model had the lowest b value. ZH 311 exhibited higher a values and lower b values (except in roots) than XY 508. The model established on ZH 311 based on stem-sheath had the highest stability, and the model established on XY 508 based on leaf had the highest stability. Relative yield (RY), nitrogen nutrition index (NNI), and cumulative nitrogen deficit (AND) were significantly correlated at different growth stages of different organs (R²>0.80) using each critical nitrogen concentration dilution curve to predict yield.DiscussionIn the high-nitrogen efficiency variety ZH 311, roots, stem-sheath, leaves, and plants showed weaker responses to AND than those of the low nitrogen-efficiency variety ZH 311 with at all growth stages. ZH 311 roots exhibited stronger responses to NNI at the early growth stage, and stem-sheath, leaves, and plants had stronger responses to NNI at the later growth stage, indicating that the high nitrogen-efficiency variety ZH 311 was not sensitive to nitrogen deficiency and was more efficient for nitrogen nutrition.